Assessing the quality of patient care: a normative decision view. (1st January 2014) - Nasim, Kanwal; Malik, Shahab Alam; Iqbal, Muhammad Zahid; Malik, Shujah Alam
This paper aims at assessing the quality of patient care by analysing the relationship between patients' perceptions of and satisfaction with service quality (SQ) in public-sector hospitals. The interaction effect of expected service quality (ESQ) is also assessed. Data collected from the patients admitted in two (for pilot study, N = 95) and five public-sector hospitals (for main study, N = 775) were analysed using SPSS. The results reveal that patients are satisfied with the SQ of hospitals. Moderating role of ESQ is also confirmed. Management of hospital should take initiatives to improve the overall service quality of patient care. Regular feed-back from patients should be taken and rules should be made considering the expectations and requirements of patients. This study attempted to examine the moderating role of ESQ in determining the patients' satisfaction. This supports the normative decision theory, as patients are found making informed decisions before selecting the hospitals. This can be of value to healthcare administration for improving SQ based on patients' feedback.